2015
DOI: 10.1002/2014jb011680
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation process of an M2 earthquake in a deep gold mine in South Africa inferred from on‐fault foreshock activity

Abstract: Using a network of sensitive high-frequency acoustic emission sensors, we observed foreshock activity of an Mw 2.2 earthquake (main shock) in a deep gold mine in South Africa. Foreshock activity, which selectively occurred on a part of the rupture plane of the forthcoming main shock, lasted for at least 6 months until the main shock. Rock samples recovered from the main shock source region showed evidence of ancient hydrothermal alteration on the main shock rupture plane, suggesting that the foreshock activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Yabe et al [78] showed that the aftershock AE events clearly delineated a plane in the PG dike with a strike of N22W and a dip of 68 • toward N68E (Figure 17). Because waveforms of the main shock recorded by the AE network were saturated in AE recordings, the main shock was analyzed using waveform data of the in-mine geophone network.…”
Section: Gold Mine Mponeng In South Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Yabe et al [78] showed that the aftershock AE events clearly delineated a plane in the PG dike with a strike of N22W and a dip of 68 • toward N68E (Figure 17). Because waveforms of the main shock recorded by the AE network were saturated in AE recordings, the main shock was analyzed using waveform data of the in-mine geophone network.…”
Section: Gold Mine Mponeng In South Africamentioning
confidence: 99%
“…Therefore, the aftershock plane is considered to correspond to the rupture plane of the main shock plane, which demonstrates clearly that the AE aftershock activity outlines the main shock's rupture plane. Kozlowska [78] show that the aftershocks occur in areas of positive Coulomb stress change as determined using rate and state based stress modeling.…”
Section: Gold Mine Mponeng In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments show that a small amount of dilatant aseismic slip can occur before seismic slip, and that earthquakes can be generated even in velocity strengthening material, which laboratory experiments suggested was unlikely . Furthermore, several current microseismic experiments in underground mines are providing insights into the complexity in small earthquake nucleation (e.g., Yabe et al, 2015). Despite the exciting results of these studies, the earthquakes generated were limited to a small number of small magnitude events.…”
Section: Knowledge Gaps Between Earthquake Theory and Observationmentioning
confidence: 99%
“…Holes were drilled from mining level 95 L, 2.9 km from surface with a rig used for underground routine drilling of geological exploration. Star: A site where normal-faulting stress regime was measured on mining level 98 L, Ogasawara et al (2012) The research sought to determine how ruptures (Mw>-4) evolve in space and time ahead of mining faces at the Cooke 4 mine and a highly stressed dyke at the Mponeng mine (Nakatani et al (2008), Naoi et al (2011Naoi et al ( , 2014 and Yabe et al (2015), in Figure 1).…”
Section: Introductionmentioning
confidence: 99%